Childhood Overweight and Obesity in Morocco: A Systematic Review - El Mossaoui, Mohamed; Barkat, Amina (International Journal of Child Health and Nutrition, 2024)
Introduction: Childhood overweight and obesity have become pervasive forms of malnutrition affecting Moroccan children, exerting significant impacts on their physical growth and psychological development. Objective: This study aims to conduct a comprehensive assessment of the epidemiological landscape surrounding childhood overweight and obesity in Morocco. Additionally, it seeks to evaluate the efficacy of national strategies and nutrition programs implemented by the Moroccan Ministry of Health. Methods: This study gathered data from reputable sources, employing a systematic review approach, including Pubmed, Science Direct, Scopus, and Google Scholar databases. The selected articles focused on overweight and obesity within the Moroccan population, with the search period spanning from 2010 to 2020. Results: The study unveiled many factors associated with childhood overweight and obesity. Intriguingly, overweight is not always synonymous with childhood obesity, though it remains a critical contributing factor. Conclusion: Childhood overweight and obesity in Morocco show severe forms of malnutrition, eliciting significant concerns within the Moroccan academic community. An urgent imperative is to enhance existing strategic plans to address this issue effectively.